Pengaruh Corporate Governance, Pertumbuhan Perusahaan, dan Media Exposure Terhadap Pengungkapan Corporate Social Responsibility - Yuliandhari, Willy Sri; Wulandari, Ninda Kusuma (Politeknik Ganesha Medan, 2024)
The purpose of this study is to ascertain how corporate governance, company growth, and media exposure affect the disclosure of corporate social responsibility, as well as how these factors interact to affect the disclosure of corporate social responsibility. A company with a non-cyclical consumer base that is listed on the indonesia stock exchange makes up the study's population. Secondary data from the indonesia stock exchange are used to collect data. With a purposeful sampling method, 31 samples were used to create the sample. The method of analysis employs multiple linear regression. According to the findings, there is a considerable relationship between corporate governance, business expansion, and media exposure and the disclosure of corporate social responsibility. board independence, board size